IN VITRO ANTIOXIDANT ACTIVITY OF ANTHOCYANINS FROM THE PERICARP OF TERMINALIA CATAPPA L. FRUITS - M. RAMA PRABHA (International Journal of Pharma and Bio Sciences, 2015)
To elucidate the pigment molecules and antioxidant activity of anthocyanins from the pericarp of Terminalia catapa L. fruits. Method: Anthocyanins were isolated from the pericarp using standard method of isolation and their antioxidant activity was measured by In vitro methods viz., DPPH assay, metal chelating activity, reducing power and H2O2 scavenging assay. Results: The anthocyanins exhibited 70.11%, 64.66% and 70.6% inhibition at 100 µg/ml against DPPH, ferrous ion and hydrogen peroxide respectively. The reducing power was found to be concentration dependent. Conclusion: The anthocyanins isolated from pericarp of Terminalia catapa could be a source of natural pigment with antioxidant property.